Kejadian Enterobiasis Pada Anak Di Dusun Kiuteta Noelbaki Kabupaten Kupang - Agnes Rantesalu; Muammar Aldizar; Meylani F. Bessie; Gabriela Haning; Father Nyong Omay; Andi Rizki Alamsyah (LPPM STIKES Mataram, 2025)
Abstract Introduction: Enterobiosis is a common infection in children and remains a significant health issue, particularly in areas with inadequate sanitation.. Objective: This study was conducted to identify the incidence of Enterobiasis in children in Kiuteta Noelbaki Hamlet, Kupang Regency. Method: This descriptive study involved 76 children aged 2–12 years using a total sampling technique. Specimen collection was carried out using the adhesive cellophane tape method and analyzed through microscopic examination. Results: 19 children (25%) of the 76 children examined, and tested positive for Enterobius vermicularis infection. Conclusion: The prevalence of Enterobiasis in the region is still high (25%), so environmental health interventions and hygiene education are needed.